DBU-catalyzed synthesis of novel 2-amino-3-nitrile-4H-chromenes - Koz, Gamze; Koz, Ömer (Walter De Gruyter Gmbh, 2017)
A simple method via the base-catalyzed Michael addition of nitroalkanes to 2-iminochromenes was developed, which leads to the production of highly functionalized 2-amino-3-nitrile-4H-chromenes in good yields.
Keywords: base catalyst; iminochromene; Michael addition; nitroalkane